2019
DOI: 10.3390/ani9100845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticle Administration on Productive Performance, Blood Parameters, Antioxidative Status, and Silver Residues in Growing Rabbits under Hot Climate

Abstract: Simple SummarySilver nanoparticles (AgNPs) were used for their antibacterial effects, which increase productive performance and immune response in poultry and rabbits. On the other hand, residues of silver in meat and the internal organs of treated animals may be toxic for human beings. The current results of using two doses of injecting AgNPs revealed that body weight significantly improved in rabbits given a low dose of AgNPs compared with control animals. For consumers’ health concerns, it is of interest to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 24 publications
4
30
0
1
Order By: Relevance
“…The decrease in cumulative body weight and other relative organ weights such as spleen of boiler chickens supplemented with SiO2@AgNPs might be due to the effect of these nanomaterials on blocking the intestinal absorption of actively transported sugars and amino acids, and reduced protein digestibility through the small intestine where mainly enzymatic activity is present as maintained by Vadalasetty et al (2018) 23 . From current results It can be noticed that the levels of SiO2@AgNPs levels had significant and insignificant effect on some parts of carcass, for instance the spleen percentages was decreased comparing with control group (p > 0.05), Bursa (not significant effect) and Thymus showed significant effect (p > 0.008), these results were partially agreeing with Abdelsalam et al (2019) 55 . Administration of SiO2@AgNPs showed a substantial and insignificant effect in all blood parameters values as found in (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in cumulative body weight and other relative organ weights such as spleen of boiler chickens supplemented with SiO2@AgNPs might be due to the effect of these nanomaterials on blocking the intestinal absorption of actively transported sugars and amino acids, and reduced protein digestibility through the small intestine where mainly enzymatic activity is present as maintained by Vadalasetty et al (2018) 23 . From current results It can be noticed that the levels of SiO2@AgNPs levels had significant and insignificant effect on some parts of carcass, for instance the spleen percentages was decreased comparing with control group (p > 0.05), Bursa (not significant effect) and Thymus showed significant effect (p > 0.008), these results were partially agreeing with Abdelsalam et al (2019) 55 . Administration of SiO2@AgNPs showed a substantial and insignificant effect in all blood parameters values as found in (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…The higher growth performance traits (body weight, ADG, ADFI and feed to gain ratio) that have been depicted by exotic breeds (NZW and Rex) compared with local Egyptian breeds (Al-Gabali) were detected in a previous most recent study [41], and this showed the genetic potential of these breeds for growth compared with Egyptian local breed..…”
Section: Discussionmentioning
confidence: 65%
“…Concerning the results of oxidative stress parameters, the current results collaborate those of Abdel-Hamid and Omar [51], who detected significant effect of genetic group on catalase separately and GPx in interaction with dietary supplementation with formic acid under heat stress (32°C ± 1). There were nonsignificant effects of breed on TAC, GPx, and malondialdehyde under heat stress [41]. The oxidative stress indicators were recorded in the serum of four exotic rabbit breeds (Fauve de Bourgogne, Chinchilla, British Spot, and New Zealand White) in Ibadan, Southwest Nigeria within July and August, and it was found that the four breeds had similar (P >0.05) serum lipid peroxidation, TAC, catalase, and GPx, whilst British Spot rabbits had a high significant (P <0.05) SOD, which suggests that this breed had the least superoxide anion scavenging ability compared with other breeds [52].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The antioxidants play an important action as protector's cells from ROS production via reducing the free radicals and disrupting the process of lipid peroxidation (Rahmani, Goliana, Kermanshahia, & Bassamib, 2018). Usage of synthetic antioxidants (vitamins and minerals) or natural antioxidants (herbs and spices) is commercially accepted, as a strategy for improving the productivity and health status of heat‐stressed rabbits (Abdelsalam et al., 2019; Daader et al., 2018).…”
Section: Introductionmentioning
confidence: 99%